Literature Review: Literasi Matematika Dengan Pendekatan Self-Regulated Learning: Distribusi Fase SRL, Analisis Dominasi Fase SRL dan Implikasinya terhadap Praktik Pembelajaran - Kurabi, M.Kasyiful; Kurniati, Nani; Azmi, Ema Suryani; Agutina, Ripki Amalia (Journal of Science Technology and Education, 2025)
Mathematical literacy is an important competency in the 21st century curriculum that requires students to be able to connect mathematics with real life. However, the results of national and international assessments show the low mathematical literacy skills of Indonesian students. This study aims to examine how the Self-Regulated Learning (SRL) approach can be used to develop students' mathematical literacy. The method used is a systematic literature study, published between 2018 and 2025. The results of the study show that SRL can improve students' abilities in understanding, managing, and applying mathematical concepts in real contexts, through three main phases: planning (forethought), implementation (performance), and reflection (self-reflection). These findings provide strategic direction for the development of more independent, reflective, and contextual mathematics learning.